2022-RA-135-ESGO Cytoreductive surgery in recurrent endometrial cancer: a new paradigm for surgical management?. (20th October 2022) - Dhanis, Joëlle; Blake, Dominic; Rundle, Stuart; Pijnenborg, Johanna M.A.; Smits, Anke
Abstract : Introduction/Background: To review the literature on the effect of surgical cytoreduction in recurrent endometrial cancer on survival and identify factors associated with improved survival. In addition, we sought to assess the effect of previous radiotherapy on surgical achievement. Methodology: This review was performed according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. We performed a search of PubMed and Cochrane Library to identify studies comparing cytoreductive surgery to medical management and studies reporting on patients receiving cytoreductive surgery as part of multi-modal treatment. Primary outcomes included overall survival and progression free survival, secondary outcomes included factors associated with improved survival. Results: A total of 11 studies fulfilled the inclusion criteria, comprising 1146 patients. All studies were retrospective studies. Cytoreduction as part of treatment for recurrent endometrial cancer was associated with prolonged overall survival and progression free survival. Complete cytoreduction was an independent factor associated with improved survival. Other factors associated with prolonged survival were tumor grade 1, endometrioid histology, ECOG performance status 0, and isolated pelvic recurrences. Factors associated with obtaining complete cytoreduction included solitary disease, tumor size <6 cm and ECOG performance status 0. Previous radiotherapy was not associated with achieving complete cytoreduction. Conclusion: Cytoreductive surgery may benefit patients meeting specific selection criteria based on a limited number of retrospective studies, with complete cytoreduction showing the largest survival gain. However, further prospective studies are needed to validate the survival benefit and aid in patient selection.